Prosocial Attitudes of Juvenile Males as Predictors of Desistance Post-Release - Liu, Beverly C. C. (Journal of developmental and life-course criminology, 2022)
This study explores how prosocial attitudes, including self-efficacy, locus of control, and readiness for change, may predict desistance across offense types for serious and violent juvenile male offenders in the USA. This study uses data from the Serious and Violent Offender Reentry Initiative (SVORI) Multi-site Impact Evaluation collected between 2004 and 2011 and uses a sample of 319 juvenile male offenders. The purpose of this study is to expand the literature on serious and violent juvenile offenders, with a focus on a selection of prosocial attitudes and whether they are contributing factors to predicting desistance after release from incarceration. The study failed to find a significant relationship between any of the juvenile prosocial attitudes and their post-release offending outcomes. Implications for theory, policy, and directions for future research are discussed.